Transcriptomic and metabolomic insights into the antimicrobial mechanisms of Murraya paniculata (L.) Jack leaf extract - Ma, Qing; Zhang, Lin; Nie, Azhen; Shi, Yini; Liu, Zhongqiu; Zhang, Rongrong; Sun, Zhongke (Frontiers in Plant Science, 2025)
The small tropical evergreen shrub, Murraya paniculata (L.) Jack (M. paniculata) exhibits inhibitory effects against a range of pathogens. However, the molecular basis for this antimicrobial activity is largely unknown. This study investigated how M. paniculata inhibits bacterial growth. Five different extracts showed variable antimicrobial potentials against four bacterial pathogens. The acetone extract of M. paniculata leaf (AEML) inhibited the growth of all pathogens, with minimum inhibitory concentration (MIC) values ranging from 200 to 400 μg/mL. Further assays on pathogenic Escherichia coli showed dose-dependent effects involving disruption of the cell wall and membrane, as indicated by increased secretion of intracellular components and propidium iodide staining. Transcriptomic analysis demonstrated that AEML regulated bacterial gene expression (357 genes upregulated and 280 downregulated), with most differentially expressed genes enriched in oxidative phosphorylation and the citrate cycle. In particular, downregulated metabolisms of thiamine and biotin metabolism—cofactors essential for energy metabolism—was downregulated. Finally, untargeted metabolomic analysis identified more than 1,000 metabolites in AEML by LC-MS/MS, including phenols and flavonoids contributing to the antimicrobial effect. Notably, more than 30 different antibiotics were detected. Taken together, M. paniculata produces versatile antimicrobial agents that exert profound effects on bacterial physiology. These findings provide novel molecular insights into the antimicrobial effects of M. paniculata.